2023
DOI: 10.3389/fnut.2023.1008822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary phenylalanine on growth performance and intestinal health of triploid rainbow trout (Oncorhynchus mykiss) in low fishmeal diets

Abstract: This study aimed to investigate the effects of phenylalanine on the growth, digestive capacity, antioxidant capability, and intestinal health of triploid rainbow trout (Oncorhynchus mykiss) fed a low fish meal diet (15%). Five isonitrogenous and isoenergetic diets with different dietary phenylalanine levels (1.82, 2.03, 2.29, 2.64, and 3.01%) were fed to triplicate groups of 20 fish (initial mean body weight of 36.76 ± 3.13 g). The weight gain rate and specific growth rate were significantly lower (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
2
3
0
Order By: Relevance
“…The results showed that dietary Phe enhanced the content of muscle fat and protein in grass carp. Similar results were found in triploid rainbow trout ( Zhang et al, 2023 ). Free amino acids (FAA) are considered taste-active compounds, participating in the Maillard reaction and imposing profound influences on the final flavor ( Reina et al, 2014 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results showed that dietary Phe enhanced the content of muscle fat and protein in grass carp. Similar results were found in triploid rainbow trout ( Zhang et al, 2023 ). Free amino acids (FAA) are considered taste-active compounds, participating in the Maillard reaction and imposing profound influences on the final flavor ( Reina et al, 2014 ).…”
Section: Discussionsupporting
confidence: 87%
“…Phenylalanine (Phe), as one of the EAAs in animals, is not only a precursor substance for protein synthesis but also participates in glycolipid metabolism in the organism as one of the ketogenic amino acids ( Guo et al, 2022 ). Previous studies have shown that an appropriate level of Phe could promote the growth of young grass carp ( Li et al, 2015 ) and triploid rainbow trout ( Oncorhynchus mykiss ) ( Zhang et al, 2023 ). Fish growth mainly involves the development of muscles ( Xiao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. aquatilis is an emerging pathogen affecting both fish and humans, causing enteritis, septicemia, and death in severe cases ( 30 , 31 , 36 , 45 , 46 ), and has resulted in significant economic losses to fish farmers in China. Recent studies indicated that the thickness of the mucosal layer, muscular layer, and intestinal villus length was decreased after bacterial infection ( 47 , 48 ), and the pathological changes were basically consistent with those of the presently studied crucian carp infected with R. aquatilis . The enzyme activities of ALT, AST, and AKP were usually used in the disease-resistance immune and pathological damage ( 49 ).…”
Section: Discussionsupporting
confidence: 84%
“…By optimizing feed formulations and supplementing effective additives, it is feasible to sustain optimal nutrition and growth in rainbow trout, even with reduced fish meal content. Previous nutritional assessments in our laboratory have shown that triploid rainbow trout can maintain normal growth and development with a fish meal inclusion level of 15% [15,16]. However, research into the effects of C. butyricum supplementation in low-fish-meal diets, particularly its impact on the immune response, intestinal inflammation-related gene expression, and microflora in triploid rainbow trout, remains scarce.…”
Section: Introductionmentioning
confidence: 99%